Surviving Hitler and Mussolini : daily life in occupied Europe - Gildea, Robert; Wieviorka, Olivier; Warring, Anette (Berg, 2006)
Surviving Hitler and Mussolini examines how far everyday life was possible in a situation of total war and brutal occupation. Its theme is the social experience of occupation in German- and Italian-occupied Europe, and in particular the strategies ordinary people developed in order to survive. Survival included meeting the challenges of shortage and hunger, of having to work for the enemy, of women entering into intimate relations with soldiers, of the preservation of culture in a fascist universe, of whether and how to resist, and the reaction of local communities to measures of reprisal taken in response to resistance. What emerges is that ordinary people were less heroes, villains or victims than inventive and resourceful individuals able to maintain courage and dignity despite the conditions they faced.The book adopts a comparative approach from Denmark and the Netherlands to Poland and Greece, and offers a fresh perspective on the Second World War.